Microsoft Azure security center - Diogenes, Yuri; Shinder, Thomas W. (Microsoft Press : Pearson Education, 2018)
Discover high-value Azure security insights, tips, and operational optimizations This book presents comprehensive Azure Security Center techniques for safeguarding cloud and hybrid environments. Leading Microsoft security and cloud experts Yuri Diogenes and Dr. Thomas Shinder show how to apply Azure Security Center's full spectrum of features and capabilities to address protection, detection, and response in key operational scenarios. You'll learn how to secure any Azure workload, and optimize virtually all facets of modern security, from policies and identity to incident response and risk management. Whatever your role in Azure security, you'll learn how to save hours, days, or even weeks by solving problems in most efficient, reliable ways possible. Two of Microsoft's leading cloud security experts show how to: " Assess the impact of cloud and hybrid environments on security, compliance, operations, data protection, and risk management " Master a new security paradigm for a world without traditional perimeters " Gain visibility and control to secure compute, network, storage, and application workloads " Incorporate Azure Security Center into your security operations center " Integrate Azure Security Center with Azure AD Identity Protection Center and third-party solutions " Adapt Azure Security Center's built-in policies and definitions for your organization " Perform security assessments and implement Azure Security Center recommendations " Use incident response features to detect, investigate, and address threats " Create high-fidelity fusion alerts to focus attention on your most urgent security issues " Implement application whitelisting and just-in-time VM access " Monitor user behavior and access, and investigate compromised or misused credentials " Customize and perform operating system security baseline assessments " Leverage integrated threat intelligence to identify known bad actors